What’s there in an n? Investigating contextual resources in small group discussions concerning an algebraic expression - Rystedt, Elisabeth; Kilhamn, Cecilia; Helenius, Ola (NOMAD Nordic Studies in Mathematics Education, 2016)
This small-case study combines a content related and a dialogical approach, in an in-depth analysis of how three 12-year-old pupils in a video recorded small group discussion construe the meaning of the letter n in an algebraic expression. The findings indicate that the pupils used a rich variety of contextual resources in their sensemaking attempt. They also tried out a wide range of interpretations of the letter indicating that their conception of an algebraic letter was rich but unstable and that the dialogue was instrumental in helping them move from primitive to more advanced interpretations. In addition to previously known difficulties of understanding letters as variables, we found that the meaning of the communicative convention ”expressed in n” proved an obstacle, and conclude that learning mathematics is as much about learning a specific communicative genre as learning about mathematical objects and relationships.